Policies and practices of inclusive education: conditions and contradictions in the daily life of a primary school - Souza, Flávia Faissal; Dainez, Débora; Smolka, Ana Luiza Bustamante; Scian, Roberta Gomes; Hulshof, Cristina (Education Policy Analysis Archives, 2014)
This paper aims analyze some of the contradictions present in the work on inclusive education, based on a group research project developed in an elementary public school in Campinas, SP, Brazil. Starting from the basic assumptions of a historical-cultural perspective of human development, we discuss the conditions for teachers’ activities and for the development of students with disabilities, aiming to understand how public policies influence educational practices. Additionally, we reflect on the impact of the research project on school life. In our analysis of empirical data from field journals and video and audio records, we point out the tensions and difficulties that permeate everyday relations inside the school, stating the limits of the proposal for inclusive education. We believe that public policies need to be targeted in order to achieve educational conditions that promote the pedagogical potential and the developmental possibilities of students with disabilities. We also emphasize the need to invest in teacher training considering their daily work within the school, as well as the importance of the creation, ownership, and availability of various resources and instruments in order to make possible the production of learning and developmental paths in educational relations.